Implementation of the ADDIE Model in Chatbot Development using Diagramflow - Nugraha , Fadhil Mureno Ega; Setiyawan, Muhammad (Journal of Technology and System Information, 2025)
This study discusses the implementation of the ADDIE model in the development of a customer service chatbot using DiagramFlow. The ADDIE model, which consists of five stages—analysis, design, development, implementation, and evaluation—is applied to ensure that the chatbot enhances customer service efficiency. The analysis stage helps in understanding the needs of both customers and the customer service team, while the design and development stages ensure the chatbot functions optimally. The implementation of the chatbot demonstrates a positive impact in reducing the workload of customer service representatives and improving user experience. The evaluation indicates that the chatbot can provide fast and effective responses, although challenges remain in understanding customer language and achieving more natural interactions. Therefore, further development is necessary to enhance the chatbot’s intelligence, allowing it to better adapt to customer needs and deliver more optimal services.